Impact of Christianity as an Ideological Instrument in the Way of Colonization: A Postcolonial Insight to Chinua Achebe's Arrow of God - Miah, Jony; Dr. Md. Abdul Halim (International Journal of Language and Literary Studies, 2024)
This article investigates the manner in which Christianity and colonialism are linked in Chinua Achebe's book Arrow of God. Furthermore, by employing a postcolonial viewpoint this paper attempts to show how European missionaries deliberately utilized Christianity to colonize the indigenous peoples of Africa. In the eyes of the majority of Europeans, colonialism advances and helps the colonized African societies, chiefly via the use of Christianity as one of its instruments. The majority of missionaries claim that this religion has nothing to do with worldly pursuits like a thirst for natural riches or colonialism, but in reality, it plays a significant cultural role in aiding the European conquest of the local Africans they have colonized. In Western discourse, Christianity was seen as a tool to liberate African people from their barbarous traditional beliefs and way of life during the colonial era. African Indigenous who have been colonized are educated and trained to lead more contemporary, civilized lives. Nonetheless, some African writers occasionally present an alternative viewpoint on Christianity. Christianity was a tool used by the colonists to further their ideological objectives. This paper explores how Christianity has been used as a tool for colonizing the Africans in Arrow of God. Renowned African novelist Chinua Achebe, a writer of postcolonial literature, contributed significantly—though controversially—to the fight against colonialism and his nation's efforts to restore its African identity. The paper is based on textual analysis. The original text Arrow of God has been used as the primary source of data and different journals, websites, online materials, and book chapters have been used as secondary sources of data.